2010
DOI: 10.1002/jcb.22587
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of dexamethasone‐conjugated linear polyethylenimine as a gene carrier

Abstract: Linear polyethylenimine (25 kDa, LPEI25k) has been shown to be an effective non-viral gene carrier with higher transfection and lower toxicity than branched polyethylenimine (BPEI) of comparable molecular weight. In this study, dexamethasone was conjugated to LPEI25k to improve the efficiency of gene delivery. Dexamethasone is a synthetic glucocorticoid receptor ligand. Dexamethasone-conjugated LPEI25k (LPEI-Dexa) was evaluated as a gene carrier in various cells. Gel retardation assays showed that LPEI-Dexa co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
2
12
2
Order By: Relevance
“…Similarly, Dex-polymer complexes (PEI25 and PEI2) were reported to have increased pDNA binding as compared to native PEI. 7,8 Enhanced hydrophobic associations in the case of Dex might explain this difference from our results. 12 Therefore, it could be concluded that whether a lipophilic substituent enhances or impedes pDNA binding might depend on substituent's nature.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Similarly, Dex-polymer complexes (PEI25 and PEI2) were reported to have increased pDNA binding as compared to native PEI. 7,8 Enhanced hydrophobic associations in the case of Dex might explain this difference from our results. 12 Therefore, it could be concluded that whether a lipophilic substituent enhances or impedes pDNA binding might depend on substituent's nature.…”
contrasting
confidence: 99%
“…However, unlike our results, Huh et al noted that chitosan‐ChA conjugates better self‐assembled under aqueous conditions due to strong hydrophobic interactions among the ChA moieties. Similarly, Dex‐polymer complexes (PEI25 and PEI2) were reported to have increased pDNA binding as compared to native PEI . Enhanced hydrophobic associations in the case of Dex might explain this difference from our results .…”
Section: Methodscontrasting
confidence: 80%
See 2 more Smart Citations
“…Dexamethasone (Dexa), an effective, synthetic glucocorticoid, could bind to the glucocorticoid receptor after cellular entry and translocate the complexes into the nucleus. [15][16][17][18][19][20] The results of these studies have confirmed that Dexa-conjugated vector/DNA complexes could be efficiently delivered into the nucleus with the glucocorticoid receptor, resulting in increased transgene expression.…”
Section: Introductionmentioning
confidence: 81%